Pelatihan Pengisian Konten Website bagi Karang Taruna di Lingkungan Kelurahan Kauman - Irmalia Suryani Faradisa; Febriana Santi W; Widhy Wahyani (Prapanca : Jurnal Abdimas, 2021)
Malang is the second largest city after Surabaya in East Java, and is one of the best colonial city planning results of the Dutch East Indies. This can be seen from the many relics of colonial architecture that still stand majestically and environmental systems that have historical value. Malang City Center in 1914 was located in kayutangan area to Malang city square. Kayutangan area of Malang city is located on Jalan Basuki rahmat gang VI, Kauman Subdistrict Klojen. Since April 22, 2018 Kayutangan village has been designated as a heritage area by the Malang city government. Kampung Kayutangan offers cultural tourism with historical education, by showing the architecture of dutch colonial heritage houses that are still preserved to this day. There are about 60 houses identified as colonial buildings. Not only the architecture of buildings, equipment or antiquities that exist there but also kayutangan village still holds many remnants of past civilizations such as the tomb of Honggo Kusumo mbah, tandak cemetery, krempyeng market, Dutch irrigation, waterways, thousand stairs and other points that have high historical value in Malang. With all its advantages as a heritage village has a social impact on the economic development in the village. Now the village is visited by many local tourists and there are also foreign tourists. Based on this, a website was created to be able to publish kayutangan village. Abdimas activities aim to train and assist kampung heritage youth in filling the content of this website so that they can update the website with the latest circumstances of the development of kampung heritage. The expected benefits of this training are: Kampung Heritage can be more famous and it is expected that the economy of the community will increase with the number of tourists visiting.